2014
DOI: 10.2188/jea.je20140002
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between hOGG1 Ser326Cys Polymorphism and Increased Body Mass Index and Fasting Glucose Level in the Japanese General Population

Abstract: BackgroundEvidence suggests that Ser326Cys, a genetic polymorphism of human 8-oxoguanine glycosylase 1 (hOGG1), is associated with insulin resistance and type 2 diabetes; however, the underlying mechanism is unclear. Recently, an animal study showed a significant association between the hOGG1 genotype and obesity, although evidence for such an association in humans is limited. The purpose of this study was to examine the association between the hOGG1 genotype and body mass index (BMI) and fasting blood glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…In human populations, a relatively common OGG1 polymorphism, Ser326Cys, is associated with reduced glycosylase activity, and has been shown to be correlated with increased body mass index and elevated total cholesterol and fasting blood glucose in Japanese individuals homozygous for the mutation [209]. Similarly, in a Mexican cohort, the Ser326Cys polymorphism was independently correlated with increased incidence of type-2 diabetes [119].…”
Section: Metabolic Diseasementioning
confidence: 99%
“…In human populations, a relatively common OGG1 polymorphism, Ser326Cys, is associated with reduced glycosylase activity, and has been shown to be correlated with increased body mass index and elevated total cholesterol and fasting blood glucose in Japanese individuals homozygous for the mutation [209]. Similarly, in a Mexican cohort, the Ser326Cys polymorphism was independently correlated with increased incidence of type-2 diabetes [119].…”
Section: Metabolic Diseasementioning
confidence: 99%
“…In the Cys/Cys genotyped individuals, body mass index was found to be higher [25]. In another study on the Japanese population, patients carrying the Cys/Cys or the Cys/Ser genotypes, HOMA-beta, an indicator of beta cell function, was decreased with improved glucose tolerance, however, among patients with the Ser/Ser genotype, it was elevated in individuals with glucose intolerance but decreased in ones with diabetes [26].…”
Section: Discussionmentioning
confidence: 90%
“…A previous study (J-MICC study) reported on the heterogeneity between the study areas. Hara et al found that the study area had a significant impact on the prevalence of obesity [ 41 ]. It is therefore important to consider the heterogeneity between the study areas.…”
Section: Methodsmentioning
confidence: 99%